The Impact of Public Capital, Human Capital, and Knowledge on Aggregate Output - Joutz, Frederick; Abdih, Yasser (Washington, D.C. : International Monetary Fund, 2008)
This paper investigates the impact of public capital on private sector output by testing and estimating an aggregate production function for the U.S. economy over the postwar period augmented to include the stock of public capital as an additional factor input. We use patent applications to proxy for knowledge/technology stocks and adjust labor hours for changes in human capital or skill. Using Johansen's (1988 and 1991) multivariate cointegration analysis, we find a positive and significant long run effect of public capital, private capital, skilladjusted labor, and technology/ knowledge on private sector output. We find that public capital accounts for about half of the post-1973 productivity slowdown, but only plays a minor role in the partial recovery of labor productivity growth since the mid 1980s. The largest contribution to that (partial) recovery comes from the knowledge stock and human capital.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet